Online frame-to-model pipeline to 3D reconstruction with depth cameras using RGB-D information - Dornelles, Thiago de Azevedo; Jung, Claudio R. (Anais da Conference on Graphics, Patterns and Images (SIBGRAPI); 2020: Anais da XXXIII Conference on Graphics, Patterns and Images, 2020)
This work presents an online pipeline for incremental 3D reconstruction and 6-DoF camera pose estimation based on colored point clouds captured by consumer RGB-D cameras. The proposed approach combines geometric matching provided by the point cloud with photometric matching provided by the color sensor through an adaptive weighting scheme that avoids eventual misalignment errors between RGB and depth data. Our experimental results indicate that the 3D reconstructions achieved by the proposed scheme are visually better or similar than a competitive approach.